(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Acne is a common chronic inflammatory skin condition that affects the pilosebaceous units is acne vulgaris. Although it usually manifests as comedones, papules, pustules, or nodules, its effects go beyond the skin and have a major impact on social and psychological well-being, particularly in young adults and adolescents. Objective: This observational study set out to determine the prevalence of moderate to severe acne vulgaris in young people in Faisalabad and investigate the relationship between the condition and social interactions, anxiety, and depression. Methodology: The study included 100 participants in total, ages 15 to 30. Using standardized instruments, information on the severity, duration, BMI, and mental health factors of acne was gathered. One-way ANOVA, independent samples t-test, chi-square test, Pearson correlation, and multiple linear regression were among the statistical analyses used. Results: The majority of participants were female (88.9%), with a mean age of 21.5 ± 2.3 years. Moderate (48.5%) and severe (31.3%) acne were most common. Acne severity showed significant positive correlations with anxiety (r = 0.48), depression (r = 0.45), and social life disruption (r = 0.41), all p < 0.001. Duration of acne also correlated with these psychological variables but to a lesser extent. Regression analysis revealed that acne severity (β = 0.42, p < 0.001) and duration (β = 0.30, p = 0.008) significantly predicted anxiety levels. Females reported higher anxiety than males (p = 0.022). Chi-square analysis showed no significant association between gender and acne severity (p = 0.127). ANOVA indicated that depression scores significantly varied with acne severity (p = 0.008). Conclusion: This study highlights the high prevalence of moderate to severe acne in young individuals, especially females, and its significant association with anxiety, depression, and impaired social interaction. These findings emphasize the need for holistic acne management approaches that incorporate mental health support alongside dermatological care.